Analisis Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan PT Brinton Sejahtera Bearindo - Zega, Yaprianus; Elmira Siska (EBISMAN eBisnis Manajemen, 2025)
PT. Brinton Sejahtera Bearindo is a company operating in the field of general trading, especially information and communication technology. The problem related to compensation is that some employees feel that they do not receive compensation according to their workload, so they are not optimally motivated to carry out their duties. The purpose of this research is to analyze the influence of compensation and work motivation partially or simultaneously on employee performance at PT. Brinton Sejahtera Bearindo. The research method is to apply a quantitative design. Sampling was carried out using a saturated sampling technique for 35 employees. The data processing method starts from data quality testing which consists of validity and reliability tests, as well as classical assumption tests. Mality, multicollinearity test, heteroscedasticity test, linearity test, hypothesis test and coefficient of determination test. The partial test results show that the t count (4,476) is greater than the t table (1,694) with a significant value of 0.00 (smaller than 0.05). The regression coefficient test data shows a positive value of 0.475, which indicates that work compensation has a positive impact on the performance of PT employees. Brinton Sejahtera Bearindo. The coefficient of determination of 0.506 shows that the influence of work compensation and work motivation on employee performance variables is 52.5%. This research can be used as a basis for developing work compensation and increasing work motivation as an important element in improving employee performance.